Zum Geschlechterverhältnis ausgewählter Schadinsektenpopulationen in Bohnenbeständen. - Heyer, Wolfgang; Chiang Lok, Maria Luisa; Cruz, Bienvenido (Contributions to Entomology = Beiträge zur Entomologie, 1988)
The proportion of the sexes in populations of Andrector ruficornis (Oliv.), Diabrotica balteata Lec., Systena basalis Duval, and Empoasca kraemeri (Ross and Moore) on bean fields follows specific laws for which obvious relations to temperature (temperature sums in diurnal degrees) or age of plants (days after seeding) could be established. They result from different migrations of the species under consideration. Only the females of E. kraemeri migrate into the bean fields. The balance of the, sexes is restored only with the formation of a new generation. With D. balteata the arrival of the males is delayed, with S. basalis that of the females. An almost balanced index of sexes throughout the whole period of vegetation is maintained by A. ruficornis.